All in one: The preparation of polyester/silica hybrid nanocomposites via three different metal-free click reactions. (5th July 2021) - Daglar, Ozgun; Çakmakçi, Emrah; Gunay, Ufuk Saim; Hizal, Gurkan; Tunca, Umit; Durmaz, Hakan
Graphical abstract: Highlights: An electron-deficient alkyne-containing polyester (PCA) was synthesized. Hybrid nanocomposites of PCA with modified silica nanoparticles were prepared. Three different click reactions were employed. The gel content of the prepared nanocomposites reached almost 88%. Mechanical and thermal properties of the nanocomposites were improved. Abstract: The development of innovative routes for the preparation of hybrid polymer nanocomposites is an active area of research for engineering applications. In this study, we have utilized three different click chemistry reactions; aza-Michael, thiol-Michael, and metal-free azide-alkyne cycloaddition reactions, and prepared hybrid nanocomposites through the reactions between electron-deficient alkyne-containing polyester and modified silica nanoparticles bearing either azide, thiol, or amine groups. The modification of the silica nanoparticles was characterized by Fourier transform infrared spectroscopy and thermogravimetric analysis. The formation of the hybrid nanocomposites was verified by measuring their gel contents. The mechanical, thermal, and optical properties of the hybrid nanocomposites were also determined. The gel content of the prepared hybrid nanocomposites reached almost 88%. Modified silica nanoparticles showed a much uniform dispersion in the polymer matrix when compared to neat silica nanoparticles. A dramatic increase both in modulus and T g values was observed for the hybrid nanocomposites.